Melacak Jejak Makna : Interpretasi Topeng Malangan Dalam Perspektif Hermeneutika Paul Ricoeur - Heri Iswandi; Sarwanto Sarwanto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2025)
This study aims to understand the deeper meaning and uncover the important values ​​contained in the Malangan Mask. This study uses Paul Ricoeur's hermeneutic analysis. The Malangan Mask is not just part of a performance; it also helps express the culture and identity of the Malang people. However, with today's developments, its meaning has become less clear because the role of masks has changed and art is often used for business purposes. By using Ricoeur's method, which looks at how meaning emerges from the three steps of prefiguration, configuration, and refiguration, we can better understand the symbols, appearances, and stories that are part of the mask. This study uses qualitative methods, observing the visual form of the mask, how it is used in performances, and speaking with local artists and cultural experts. The findings of this study indicate that the Malangan Mask explains the relationship between stories and real life, and contains messages about living a balanced life, having wisdom, and Javanese beliefs. This perspective on masks shows that masks are not just beautiful objects, but a living part of culture that can change and be understood differently depending on the context.